Multiband Antenna for Wireless Applications Including GSM/UMTS/LTE and 5G Bands - Amirreza Jalali Khalilabadi; Ata Zadehgol (Applied Computational Electromagnetics Society Journal (ACES), 2019)
A simple ultra thin multiband antenna is introduced. The proposed antenna with four bands covers many wireless applications. The proposed antenna has simple configuration including two open L-shaped slots to create resonat mode at GSM and GPS bands and also two rectangular slots on the radiating element for creating multi resonant modes to meet the specifications of mentioned frequency bands. According to the simple, small and planar configuration, the proposed antenna design is inexpensive and can easily be integrated with the other microwave circuit boards. The proposed antenna has the small size of 10 mm and the total size of 120 mm x 60 mm x 0.5 mm, promising to be used widely in compact and ultra slim handsets.